Faktor Kreativitas dalam Pengembangan Model Inkubator Bisnis di Era Digital - Anna Pudianti; Anita Herawati; Anna Purwaningsih (Universitas Negeri Surabaya, 2018)
A business incubator is a program to encourage the emergence of students entrepreneurs in various universities, including Universitas Atma Jaya Yogyakarta. The model applied in generating new entrepreneurs through business incubators at Universitas Atma Jaya Yogyakarta is described in three (3) stages of pre-incubation, incubation, and post-incubation. In the third stage of the incubation process, post incubation, the students have been assessed their readiness before finally tenant plunge as an entrepreneur. In the previous study, the motivation or desire to become an entrepreneur is a major factor to support success in business. However, in the next stage to support business sustainability, especially in the digital era as it is today, the strong capital motivation is not enough. This study aims to examine more deeply the capabilities that must be built to support business sustainability, especially in the digital age with all the technological advances. The qualitative approach is used by using successful tenants as case studies of several types of business, in order to enrich the results of the research. Triangulation and member check processes are applied to generate the results of the research. The resulting model of this study is a refinement of the initial model by emphasizing the sustainability factor of business in the digital era that emphasizes the importance of creative ability and thinking ahead.